Burdened virtues : virtue ethics for liberatory struggles - Tessman, Lisa, 1966- (Studies in feminist philosophy., 2005)
This deeply original and provocative work looks at the concerns of traditional feminist scholarship from the perspective of Aristotelian virtue ethics. Her subject is the moral life and the self under duress - how human beings exercise their moral agency within the constraints of oppressive social structures.